Contrast bath-induced neurite outgrowth in PC12m3 cells via the p38 mitogen-activated protein kinase pathway. Issue 10 (October 2019) - Motoda, Hirotoshio; Hiragami, Fukumi; Kawamura, Kenji; Inoue, Shigeki; Gomita, Yutaka; Kano, Yoshio
Abstract: We investigated the differentiation and activation of p38 MAPK induced by contrast bath in drug-hypersensitive PC12m3 mutant cells. The rate of neurite outgrowth in PC12m3 cells induced by contrast bath was much higher than that induced by warming or cooling alone or that induced by two warmings with an interval of room temperature, indicating that contrast bath has a synergistic effect. The results of an experiment using a p38 MAPK inhibitor, SB203580, showed that neurite outgrowth of PC12m3 cells induced by contrast bath is p38 MAPK-dependent. Moreover, p38 MAPK activity induced by contrast bath was greater than that induced by warming or cooling alone, indicating that the synergistic effect of a contrast bath on neurite outgrowth depends on the activity of p38 MAPK. Since calcium ions are involved in the activations of P38 MAPK, we investigated the effect of the TRP ion channel inhibitor (Capsazepine) that inhibits calcium influx in the cells. Neurite outgrowth induced by contrast bath treatment was greatly suppressed by the addition of Capsazepine. These findings suggest that calcium dependent activation of the p38 MAPK pathway induced by contrast bath is responsible for the neurite outgrowth of PC12m3 cells. Abstract : Neuroscience; Cell biology; Cell culture; Cell differentiation; Contrast bath; Neurite outgrowth; p38 MAPK; Warming; Cooling